Aspergillus niger AN 400 como inóculo de reatores em batelada para remoção do corante vermelho do congo em meio aquoso sintético - Wanderley, Carlos Ronald Pessoa (2007)
The species Aspergillus niger AN 400 has been inoculated in batch in order to remove Congo Red dye from the synthetic environment and study the treatment efficiency in the presence and absence of glucose and the biomass immobilization effect on the process optimization. It has been applied 84 reactors, produced and held in a screw top container of glass, which had a useful capacity of 1,5 L, whilst the air was supplied by small compressors. The experiment lasted a period of 25 days and the reactors without support medium; 14 control reactors with dispersed fungal biomass on which was added glucose (1 g/L); 14 reactors with immobilized fungal biomass and 14 reactors with immobilized fungal biomass on which was added glucose (1 g/L). The results obtained demonstrated that the greatest efficiency in removing the dye occurred in the reactors containing immobilized biomass in a environment with glucose concentration (87%) or not (85%). The glucose considering the utilized concentration has not performed any influence on the process efficiency. The organic matter removal which was assigned to the likely presence of by products originated by the dye and compounds expelled in the environment by microorganisms. The immobilization of the biomass in the polyurethane foams was determinant to the process efficiency as fungus was in a biofilm shape, representing a mechanism against the toxic effect of the pollutant.